2006
DOI: 10.1007/s10722-006-9165-6
|View full text |Cite
|
Sign up to set email alerts
|

Proline accumulation as a response to salt stress in 30 wheat (Triticum aestivum L.) cultivars differing in salt tolerance

Abstract: The effects of NaCl salt (EC = 16 dS m -1 ) on water potential, and accumulation of proline, Na + and K + in leaves on the main stem of 30 wheat cultivars (Triticum aestivum L.) at awn appearance and 20 days after anthesis (20 DAA) were evaluated in a greenhouse experiment. Plants were arranged in a according to a randomized complete block design with factorial treatments in three replications. Proline accumulation at 20 DAA increased with increasing salt stress. This increase was 27.4-fold with the salt-sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 29 publications
9
30
0
1
Order By: Relevance
“…Table 3 shows that salinity levels (S1 and S2) caused significant and gradual increases in the proline content of sunflower two cultivars leaves with increasing salinity levels compared with control plants (S0). The increase in proline levels due to salinity was also demonstrated by Poustini et al, (2007). Proline accumulates in larger amounts than other amino acids in salt stressed plants (Abd El-Samad et al, 2011;Taie et al, 2013 andAbdelhamid et al, 2013a).…”
Section: Changes In Some Osmoprotectantmentioning
confidence: 82%
“…Table 3 shows that salinity levels (S1 and S2) caused significant and gradual increases in the proline content of sunflower two cultivars leaves with increasing salinity levels compared with control plants (S0). The increase in proline levels due to salinity was also demonstrated by Poustini et al, (2007). Proline accumulates in larger amounts than other amino acids in salt stressed plants (Abd El-Samad et al, 2011;Taie et al, 2013 andAbdelhamid et al, 2013a).…”
Section: Changes In Some Osmoprotectantmentioning
confidence: 82%
“…The reports about the role of proline on salinity tolerance are different. Some researchers indicated that there are no relations between proline content and salinity tolerance (Lutts et al 1996;Poustini et al, 2007). Lutts et al(1996) found no relationship between proline content and salt tolerance in rice cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this parameter has been supported as a criterion of salt stress tolerance (Ashraf and Harris, 2004). However, some researchers have found that there is no correlation between leaf proline and salt tolerance (Poustini et al, 2007;Lutts et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, leaves of the salttolerant line TNC 1.8 accumulated more Na in comparison with leaves of the sensitive line TNC 11.9. These results suggested that proline accumulation itself is not sufficient to confer salt tolerance (Poustini et al 2007). This led us to hypothesize a mechanism of leaf vacuolar Na sequestration within the tolerant line TNC 1.8 under salt stress (Debez et al 2006).…”
Section: Discussionmentioning
confidence: 99%